KONSELING SUFISTIK UNTUK MENINGKATKAN MOTIVASI HIDUP PADA SEORANG PASIEN STROKE: (Studi Eksperimen di Desa Hargomulyo Kecamatan Sekampung Kabupaten Lampung Timur) - Agung Muhammad Iqbal; Kholis Khoirul Huda; Endah Trianavi (Program Studi Tasawuf dan Psikoterapi Fakultas Ushuluddin Universitas Annuqayah Guluk-Guluk Sumenep, 2023)
Stroke is brain damage that appears suddenly, progressively and rapidly due to non- traumatic brain blood circulation disorders. Stroke was the second highest cause of death in the world in 2015 and the highest cause of death in Indonesia in 2014 (1); The aim of this research is to find out what the process of implementing Sufistic counseling is to increase the life motivation of a stroke patient in Hargomulyo village, Sekampung District, East Lampung Regency. , To find out what the physiological and psychological conditions of stroke patients are like after being given the application of Sufistic counseling in Hargomulyo village, Sekampung sub-district, East Lampung regency (2); This research uses qualitative research methods with a field research approach. The data sources used were primary data sources that used the snowball sampling technique in this research, namely the NS informant, the NS informant's wife, and the three children of the NS informant. Meanwhile, secondary data sources use journals, articles, books, the internet, notes and documentation. Data collection techniques use interviews, observation and documentation. As well as data analysis techniques using data reduction, data presentation, and drawing conclusions (3); The results of this research are: the process of implementing Sufistic counseling to increase life motivation in a stroke patient in Hargomulyo Village, Sekampung District, East Lampung Regency can be carried out in several stages, namely Takhalli, Tahalli, and Tajalli; There was an increase in motivation to live in stroke patients who in this study were NS informants after being given sufistic counseling, which was seen from the results of NS informant meetings conducted by researchers which showed that the condition improved gradually; There was an improvement in the physiological condition of NS informants, such as starting to be able to walk, being able to sit and eat on their own and doing light activities. Meanwhile, regarding the psychological condition of informant NS, he felt calm and enthusiastic about recovering from his stroke (4).